Violência contra a mulher: atuação dos profissionais de saúde acerca da notificação compulsória nos territórios do campo, da floresta e das águas - Rejane Antonia Costa dos Santos (2016)
The violence against women, phenomenon of high prevalence, is recognized by the national and international organizers as violation of Human Rights. The violence that hits women of rural territories, presents itself in a wicked and unseen way. During the last decades, it was noted and improvement in the public polices and law about the violence against women. The obligatory part notification of the violence established through the law 10.778 of 2003 is powerful instrument of epidemiologic surveillance. This study is aligned to the Project with focus in the Integral Attention to the Woman Health in situation of the violence, the project “For them ” from the Nucleus of Health Promotion and FM/UFMG to the Health Ministery. It is about a cross-sectional study of quantitative approach that had as its goal to analyze the performance of Health Professionals about the compulsory notification of violence in the field, forest and water territories. The data collection was through the application of a semi-structural questionnaire. It was analyzed 438 questionnaires. The results show a prevalence of female sex. The nursing, the professional category with the biggest percentile of participation. The majority of the participants is between 21 and 40 years. 79,6% of the participants have graduation or post graduation. For the confirmed case, the Social Service and the Psychology were the categories that most notified. The tertiary attention showed the biggest percentile of notification in relation to the other levels. The highest degree of instruction appeared as a variable that can be associated to the confirmed case of the professional in notifying the cases of violence against the women. It was noted a favorable association between the offer of capacitation and the act of notify as well as the guaranty of necessary resources to the actions of combat to violence. Several difficulties were appointed in relation to the fill of an obligatory notification form, being the non-existence of notification form in the Health Unity, lack of capacitation for the staff were the main obstacles showed. The study demonstrated a not understanding from the professional to the legal and practical aspect of the notification of the violence against woman. The results suggest a sub-notification of the violence cases committed against woman. The gap in the academic training of the health professionals, the lack of capacity and as not assure of the necessary resources to the actions of combat against violence, can be associated with the difficulty in identifying, detecting the violence cases as well as the realization of the compulsory notification of violence. So, we have to discuss the necessity of continuous achievement of the capability for the professional of health attention, the importance of sensitize them and the network with the intersectional pacts. In summary, to become visible the problem of violence against woman.